Trajectories of Posttraumatic Growth and Associated Characteristics in Women with Breast Cancer. Issue 5 (19th March 2015) - Danhauer, Suzanne C.; Russell, Greg; Case, L. Douglas; Sohl, Stephanie J.; Tedeschi, Richard G.; Addington, Elizabeth L.; Triplett, Kelli; Van Zee, Kimberly J.; Naftalis, Elizabeth Z.; Levine, Beverly; Avis, Nancy E.
Abstract: Background: Cancer survivors may experience posttraumatic growth (PTG), positive psychological changes resulting from highly stressful events; however, the longitudinal course of PTG is poorly understood. Purpose: The purpose of the present study was to determine trajectories of PTG in breast cancer survivors and associated characteristics. Methods: Women ( N  = 653) participating in a longitudinal observational study completed questionnaires within 8 months of breast cancer diagnosis and 6, 12, and 18 months later. Group-based modeling identified PTG trajectories. Chi-square tests and ANOVA detected group differences in demographic, medical, and psychosocial variables. Results: Six trajectory groups emerged. Three were stable at different levels of PTG, two increased modestly, and one increased substantially over time. Trajectory groups differed by age, race, receipt of chemotherapy, illness intrusiveness, depressive symptoms, active-adaptive coping, and social support. Conclusions: This first examination of PTG trajectories in US cancer survivors elucidates heterogeneity in longitudinal patterns of PTG. Future research should determine whether other samples exhibit similar trajectories and whether various PTG trajectories predict mental and physical health outcomes.